Hubungan Status Gizi dengan Perkembangan Motorik Kasar Pada Balita Umur 1-5 Tahun di Desa Pucangombo Kecamatan Tegalombo Kabupaten Pacitan. - Sumini Sumini (Akbid Harapan Mulya Ponorogo, 2018)
Based on the data SKDN September 2015 in the village of Pucangombo district of Tegalombo, district of Pacitan , there were 132 children, the number of children who weighed consists of 3 children (2.5%) with poor nutritional status, 10 children (8.3%) with malnutrition status and 107 children (89.16%) with good nutritional status. Based on data from the nutritional status of infants, infants with malnutrition status progress has not in accordance with their age. Nutritional status of children influence the development of gross motor development at the children, so it can determine further developments. Based on preliminary study on 26 September 2015 in the village of Pucangombo Tegalombo Pacitan from 10 children found 8 respondents had good nutritional status, with of appropriate gross motor development, 2 respondents less nutritional status, with gross motor development of the doubts. This study aims to determine the relationship of nutritional status and gross motor development in under five year children. Quantitative research with cross sectional study design. This study conducted in the Village of Pucangombo Tegalombo Pacitan in September 2016. The population was children aged 1-5 years amounted to 90 children and 72 children as with samples taken by accidental sampling techniques. The independent variable was nutrient status and the dependent variable was gross motor development. Instruments with observation sheet, microtoa, scales, and KPSP. Data analysed by Spearman Rank at the 0.05 level of significance. The results of this study indicated that the nutritional status of children the majority of 62 respondents (86.1%) has good nutritional status. Gross motor development in children aged 1-5 years almost entirely 63 respondents (87.5%) with appro priate development. There was a relationship of nutritional status with gross motor development in children aged 1-5 years in the village of the t Pucangombo Tegalombo, Pacitan district, with a significance level of p <0.005 it was 0.000 with a coefficient correlation of 0.925, which means the level of closeness was very strong. Based on the results of the study are expected to mothers add insight and knowledge on nutrition of children under five nutritional needs are met in an optimal and gross motor development of infants according to age.